(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
In Uke River, Karu Local Government Area, Nasarawa State, Nigeria, a six-month research was carried out between January and June 2023 to examine the gills and intestinal helminth and protozoan parasites of White Catfish (Ameiurus catus). A total of 100 fresh Ameiurus catus fish samples of both sexes, were obtained from the fishermen and conveyed to the Zoology laboratory of Nasarawa State University for examination. The fishes were processed and examined using gills, oesophagus, intestine and rectum. Twenty-two (22) out of 100 fishes were found to be infected with helminth and protozoan parasites and a total of 31 parasites were isolated belonging to protozoa (Eimeria spp, Hexamita spp, Protoopalina spp), nematode (Procamallanus spp), trematode (Dactylogyrus spp), Cestode (Diphyllobothrium latum, Bothriocephalus claviceps) taxonomic groups. The findings indicated that Ameiurus catus intestine contained a greater quantity of fish parasites (96%). A nematode (Procamallanus spp.) was found to have the highest prevalence of 45.16%. Although the Chi square results showed no significant difference (p>0.05), the prevalence in Ameiurus catus was greater in female samples (63.64%) compared to male samples (36.36%). Fish weighing between 151-200 g (46.14%) and measuring between 21-30 cm (28.57%) had the highest percentage of parasite infection. Going forward, it is imperative to properly cook Ameiurus catus from the Uke River to prevent the spread of parasites to consumers. Additionally, it is advisable to steer clear of any potential actions that could contribute to the parasite predominance near the water body.